Kinetics of humoral response to Pasteurella multocida in buffaloes against combined foot-and-mouth+haemorrhagic septicaemia vaccine - RUSTAGI, NEENA; KAKKER, NARESH KUMAR; SHEORAN, SUMAN; SANTOSH, PATIL CHANDRASHEKHAR; DAHIYA, SWATI; GUPTA, AKHIL KUMAR (The Indian Journal of Animal Sciences, 2023)
The present study reports kinetics of anti-P. multocida antibody (Ab) response at monthly intervals in Murrah buffaloes of different age groups vaccinated against combined Foot-and-mouth disease+haemorrhagic septicaemia (FMD+HS) vaccine. A total of 60 Murrah buffaloes of three age groups having 20 animals each: calves, heifers and adults were used to monitor anti-P. multocida Ab response at monthly intervals using single dilution indirect ELISA. The percentage of adult buffaloes protected were found to be the highest during all the six months post-vaccination followed by heifers and calves. The protective mean Ab titres were maintained up to six months post-vaccination for heifers and adults but not for calves. The F value (the ratio of two mean squares) for pre- and all the six month(s) post-vaccination and all the three age groups was significantly higher. Pearson Chi square value for pre-vaccination and all the six months except three months post-vaccination was significantly higher. Pearson correlation value was significantly higher with positive linear relationship. The data in the present study indicated that the combined FMD+HS vaccine was found to be effective in buffaloes of all age groups at government organised farm and could be an ideal approach in field conditions under Livestock Health Disease Control Program run by the Government of India.